eNOS3 - As One Of The Genetic Aspects Of The Development Of Chronic Kidney Disease - Tursunova L.D; Jabbarov O.O. (Zien Journals, 2024)
Chronic kidney disease (CKD) affects approximately 10% of the global adult population. Various genetic and environmental risk factors contribute to kidney disease, complicating the identification of underlying pathophysiologic mechanisms. CKD is based on the development of nodular or diffuse glomerulosclerosis, with its terminal stage characterized by chronic renal failure (CRF). This article discusses the clinical and genetic aspects of CKD and their relationships in the early stages of the disease, as well as the cumulative effect of metabolic, hemodynamic, and genetic factors on disease development.
Keywords: chronic kidney disease; endothelin-1; gene; polymorphism